The experience of women combining fertility treatment and paid employment: women's narratives - Walker, Serena Anne (Auckland University of Technology, 2011)
The use of fertility treatments, including in-vitro fertilisation (IVF) has increased significantly in the past three decades (Wang, Chambers, Dieng, & Sullivan, 2009) as has the proportion of women in the workforce (Statistics New Zealand, 2006). Psychological implications have been associated with fertility treatments, including psychological distress, depression, and identity issues (Ulrich & Weatherall, 2000). Research has alluded to the challenge for women combining fertility treatment and paid employment. However, no targeted research has focused specifically on this. Using a narrative approach informed by a social constructionist and third-wave feminist lens, this study sought to explore how combining fertility treatment and paid employment was experienced by women. Employing a narrative perspective defined as holistic-content (Lieblich, Tuval-Mashiach, & Zilber, 1998), individual narratives were analysed for unique themes and motivations. Final analysis was undertaken with a thematic narrative analytical approach (Riessman, 2008). Themes such as private versus public narratives, failing as a woman and related identity challenges were observed. It is hoped that the findings discussed could assist mental health practitioners in supporting this cohort and may offer insights into appropriate work-place policy development.
Keywords: Narrative; IVF; Psychology; Identity